Stress reduction in thesis completion through peer tutoring method - Astuti, Budi; Purnama, Diana Septi; Laksana, Eko Pramudya (Psychology, Evaluation, and Technology in Educational Research, 2019)
This study aims to reduce stress in the completion of thesis through peer tutoring method in student of the Guidance and Counseling Study Program, UNY. This research is a classroom action research. The research subjects were 70 Guidance and Counseling Study Program students. Sampling techniques used purposive technique. Data collection used stress scale in the completion of thesis and observation guideline. The result of the pretest with the scale of stress in the completion of the thesis obtained a number of 14 students who were given an action. Data analysis technique used quantitative technique. The results showed a decrease in stress level in Guidance and Counseling student through peer tutoring method. This was indicated by the pretest average score of 104.8 (high category). After being given the action in cycle I, the average post test I score was 90.3 (medium category). This means that in cycle I there was a decrease in the average score of 14.5%. Provision of action continued in cycle II with the result of post test II obtained an average score of 72.2 (low category). This means that in cycle II there is a decrease in the average score of 18.1%. The decrease in the average score in the post test I and II obtained a total of 32.6%.